2011
DOI: 10.1590/s0100-06832011000400040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbiological attributes of an oxisol treated with successive applications of sewage sludge¹

Abstract: SUMMARYStudies on sewage sludge (SS) have confirmed the possibilities of using this waste as fertilizer and/or soil conditioner in crop production areas. Despite restrictions with regard to the levels of potentially toxic elements (PTE) and pathogens, it is believed that properly treated SS with low PTE levels, applied to soil at adequate rates, may improve the soil chemical and microbiological properties. This study consisted of a long-term field experiment conducted on a Typic Haplorthox (eutroferric Red Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
(23 reference statements)
2
9
1
9
Order By: Relevance
“…Several authors consider the sludge residue as low-K, as it is found predominantly in the ionic form, which tends to remain in solution during the process of wastewater treatment, and chemical complementation with this element is constantly recommended (Bueno et al, 2011;Guedes et al, 2006;Simonete et al, 2003). However, in the present study, K could not be considered a limiting element of productivity, because the quantities added into the soil by the treatments solarized, composted, vermicomposted and limed were, respectively: 0.7, 4.2, 3, 1 and 8.9 times the recommended.…”
Section: Stabilization Methodsmentioning
confidence: 99%
“…Several authors consider the sludge residue as low-K, as it is found predominantly in the ionic form, which tends to remain in solution during the process of wastewater treatment, and chemical complementation with this element is constantly recommended (Bueno et al, 2011;Guedes et al, 2006;Simonete et al, 2003). However, in the present study, K could not be considered a limiting element of productivity, because the quantities added into the soil by the treatments solarized, composted, vermicomposted and limed were, respectively: 0.7, 4.2, 3, 1 and 8.9 times the recommended.…”
Section: Stabilization Methodsmentioning
confidence: 99%
“…The optimal Ca:Mg ratio may be variable according to the crops. Bueno et al (2011) mentioned that the ideal ratio may range, but generally, the authors consider a Ca:Mg ratio in the range of 3:1 or 4:1 to be optimal because these ratios are found in most naturally highly fertile soils. Thus, significant changes, like those observed in this research, may compromise the nutrient balance of the soil and consequently hinder plant development.…”
Section: +mentioning
confidence: 99%
“…Diversos trabalhos demonstraram os efeitos benéficos do lodo nas propriedades físicas, químicas e biológicas do solo (Simonete et al, 2003;De Maria et al, 2007;Bueno et al, 2011), com reflexos na nutrição das culturas e, consequentemente, na produtividade.…”
Section: Introductionunclassified